A Novel Shared Protection Scheme Based on Aggregate Wavelength in High Speed Networks. (19th November 2014) - Oberoi, Anshu; Sohal, J. S.; Kaler, R. S.
Abstract : We propose novel analytical model of dynamic link cost evaluation in IP over WDM networks. We suggest disjoint path algorithm for the primary and backup path based on wavelength aggregate information, to provide shared backup. We show the optimality of pair selected because of joint optimization of the pair paths. The shareable capacity factor is introduced to establish the effect of load balancing on resources. We compared our simulation results with that of separate protection at connection and showed improvement on resource utilization performance of the network. We also study the blocking probability of proposed scheme.